ANALISIS PRAGMATIK DALAM PENGGUNAAN BAHASA IKLAN DI SURAT KABAR THE JAKARTA POST ONLINE - Dias Andris Susanto; Pipit Mugi Rahayu (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2014)
The purpose of this study are to describe and explain: 1) to determine how the use of the types of speech acts in the language of the ads found in the newspaper The Jakarta Post Online, 2) to determine how the process or how the formation of the language of advertising in letter The Jakarta Post online news as linguistic teaching materials. Research Design in this research was descriptive qualitative, which means providing indepth explanation of the phenomenon or object in a systematic way, based on the facts and accuracy (Moleong,2006:5). The authors applied this research method inorder to determine how to use the types of speech acts (speech act) in the language of the ads found in the newspaper The Jakarta Post Online, and how the formation of the language of advertising in the newspaper The Jakarta PostOnline. The Jakarta Post Online as the subject of this study .Object of this research was thatthere were ads on the newspaper The Jakarta Post Online".The following discussion of the study as a pre-supposition that the authors used the adsthey generally use two clauses (contained in 10 ads), and only one ads which used three clauses,namely ad restaurant Seafood House. Locutionary acts /illocutionary meaning, in outline form,the advertising writer intended to give statements about the advertised product, foe readers,illocutionary acts / illocutionary meaning, each of these ads had already targeted and specific targetedfor its prospective users. Perlocutionary acts / perlocution meaning has meaning as if the two-wayscommunication between the advertised product with potential buyers. Implicate happened is all theads implied that the advertised product is not a regular product, but they are the selected product andthe best.Suggestions related to the results of research are as follows: pragmatics is a science that isvery beneficial to the world of advertising for a product that was introduced in the community must beaccompanied by the sentence / speech / word which is able to make the prospective buyer / userinterested and decided to purchase / use these products, Science pragmatic needs to be introduced andtaught in the course is primarily for students of English Education in order to understand thecontext of what happened around them. Furthermore, the research and in-depth associated withadvertising and pragmatic needs to be held to answer curiosity more about The scientific treasures.Keywords: Pragmatics, Language Advertising, The Jakarta Post Online.